A numerical study with experimental validation of liquid-assisted fluidization of particle suspensions in a HydroFloat cell. (April 2019) - Islam, Md. Tariqul; Nguyen, Anh V.
Graphical abstract: Highlights: Fluidization of spherical and non-spherical particles is investigated. 3D simulation results agree with experimental data. Non-spherical particles show a low distribution of volume fraction. Non-spherical particles show a high efficiency of energy transfer. Semi-empirical correlation for overall particle volume is obtained and validated. Abstract: Fluidization can assist in coarse particle flotation. Here the dynamic behaviors of three-dimensional flows of particle suspensions (without air bubbles) in the counter-gravity regime in a HydroFloat cell with a circular cross-section are numerically studied by using the Eulerian-Eulerian approach with the RNG k−ε turbulence model. The kinetic theory of granular flow is adapted to analyze the particle behaviors. Simulation results are validated by using a laboratory-scale HydroFloat cell. The effect of superficial liquid velocities on the fluidized beds of spherical and non-spherical particles is investigated. The predicted results are within 4% of experimental results of bed expansion. The pressure drop and bed expansion of non-spherical particles are higher than those of spherical particles. Distributions of time-averaged particle axial velocity, particle volume fraction, particle kinetic energy, liquid turbulent kinetic energy, and dispersion rate are examined. The simulation results show that the particle kinetic energy is high near the column wall and low in the central region. The energy flows and the efficiency of energy transfer from the liquid phase to the solid phase in the fluidized bed cell are calculated and examined. Finally, the obtained data are analyzed to develop a correlation for the overall particle volume fraction, which would be useful for further studies of three-phase bubble-particle fluidization in flotation.